Metropolitan Landscapes. Towards a Shared Construction of the Resilient City of the Future. - (:unkn) unknown (Springer, 2021)
This edited volume covers many aspects of the Metropolitan Landscapes. Solutions are needed to meet the demand of the citizens of a renewed metropolitan region landscape. It opens up discussions about possible toolkits for strategic actions based on understanding the territory from geographical, urban, architectural, economic, environmental, and public policy perspectives. This book intends to promote the Metropolitan dwelling quality, ensuring human well-being proposing a discussion on the resilient articulation of the interface space among the city's infrastructure, agriculture, and nature. This book results from the Symposium: Metropolitan Landscapes that MSLab of the Politecnico di Milano and ETSA (Sevilla) organized at the IALE 2019 Conference (Milan, July 2019) to manage radical territory transformation with a strategic vision. The widespread growth of urban areas indicates the importance of building resilient sustainable cities capable of minimizing climate-change impact production. The Symposium aimed to discuss the Urban Metabolism approach considering the combination of Landscapes set in a single Metropolitan Ecosystem. Accordingly, new design strategies of transformation, replacement or maintenance can compose Urban-Rural Linkage patterns and a décalage of different landscape contexts. Ecological interest in environmental sustainability, compatibility, and resilience is not tied exclusively to the balance between production and energy consumption. Thus, it is the integration over time and at several scales of the urban and rural landscapes and their inhabitants that nourish the Metropolitan Bioregion. Moreover, the Metropolitan Landscape Book's research hypothesis is the need for a Glossary, strengthening the basis of understanding Metropolitan Landscape's complexity.
Keywords: Metropolregion; Metropole; Großstadtregion; Stadtlandschaft; Stadt-Land-Beziehung; Urbanismus; Landschaftsanalyse; Landschaftsentwicklung; Nachhaltige Entwicklung; Resilienz; Morphologie; Kartographie; Stadtgrün; Metabolismus; Ökosystem; Soziale Ungleichheit; Umweltgerechtigkeit; Grüne Infrastruktur; Bioregion